WILDLIFE USE IN LAPUA COMMUNITY OF KAUREH, PAPUA - WEYAH, WES; KEILUHU, HENDERINA JOSEFINA; KARIM, ADITYA KRISNA (Jurnal Biologi Udayana, 2018)
A wildlife study to find out about hunting wildlife was taken in Lapua Community, Kaureh, Papua. Specific purpose of the research was to obtain the information about wildlife species hunted, hunting techniques, and utilizations of hunted animals by the community. The study was taken place in September-October 2015, used survey method with interview techniques.  The study found out about 19 species of wildlife as common hunted species, which could be grouped into 31.58% protected by Indonesian Law, 52.63 % usually used for self-consumption, and 68.42 % were birds.  People in Lapua have their own traditional wisdom in hunting activities, which they know as active hunting which consists of eye-hunting ( Hwe ), hunting with dogs ( Seeht/kenang ), skilled hunting ( Mbree ), and imitate animal sounds ( Sukwe ), while in passive hunting ( Ptia ) they use foot snares, confinement and bird nets.  Hunting equipments for the community’s traditional hunting are spears ( Tumuayuja ), bows (Dyi ) and arrow ( Sii ), rattan strings ( Wii ) and wood for mesh materials. The hunted animals are usually for self-consumption and to be raised up and for sale.